The properties of paper from Kenaf bast fiber according to 20%, 25% and 30% active alkali using soda-aq pulping - Herman, Amrah; Mohamed Nudin, Faezah (2012)
Pulping of Kenaf bast fiber (Hibiscus cannabinus L) by Soda -AQ pulping was studied in order to investigate the effect of active alkali levels (20%, 25% and 30% AA) on the freeness of pulp and also paper properties (tensile index, bust index, tear index and bulk). The results shows that the different level active alkali affected the properties of pulp and paper. The 25% of active alkali produce the highest value of Freeness (643ml), tensile index (33.68Nm/g), burst index (0.24MPa) and tear index (23.56 mNm2/g) but the bulk of paper increases with the increases of active alkali.